POSITIONING EVALUATION WITH GNSS USING REALTIME PRECISE POINT POSITIONING METHOD FOR MINING MAPING SURVEY - Wisnu Wardhana, Gunawan (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2022)
Real Time Precise-Point Positioning (RT-PPP) is a relatively new method for satellite-based positioning or better known as the Global Navigation Satellite System (GNSS). RT-PPP has similarities with PPP in terms of data accuracy and precision because it was developed from the previous method called Precise Point Positioning (PPP). However, RT-PPP has an advantage in real time because it gets correction from the L-band in the Satellite Based Augmentation System (SBAS). This study aims to evaluate the RT-PPP method for mining surveys. The precision evaluation was carried out repeatedly for 7 days at specific points, while accuracy testing was compared with the static differential method at 11 points spread over the mining area. The results showed that the standard deviation of the RT-PPP method was 1.0 cm and 1.1 cm in the east and north, 3 cm in elevation. The accuracy test shows 17.5 cm for the RMSE horizontally and 6.2 cm vertically.